In situ and Operando Tracking of Microstructure and Volume Evolution of Silicon Electrodes by using Synchrotron X‐ray Imaging. Issue 1 (31st October 2018) - Dong, Kang; Markötter, Henning; Sun, Fu; Hilger, André; Kardjilov, Nikolay; Banhart, John; Manke, Ingo
Abstract: The internal microstructure of a silicon electrode in a lithium ion battery was visualized by operando synchrotron X‐ray radioscopy during battery cycling. The silicon particles were found to change their sizes upon lithiation and delithiation and the changes could be quantified. It was found that volume change of a particle is related to its initial size and is also largely determined by the changing surrounding electron‐conductive network and internal interface chemical environment (e.g., electrolyte migration, solid–electrolyte interphase propagation) within fractured particles. Moreover, an expansion prolongation phenomenon was discovered whereby some particles continue expanding even after switching the battery current direction and shrinkage would be expected, which is explained by assuming different expansion characteristics of particle cores and outer regions. The study provides new basic insights into processes inside Si particles during lithiation and delithiation and also demonstrates the unique possibilities of operando synchrotron X‐ray imaging for studying degradation mechanisms in battery materials. Abstract : Prolonged expansion : The internal microstructure of a silicon electrode was visualized by operando synchrotron X‐ray radioscopy during battery cycling. A prolongation of expansion was discovered, whereby some particles continued expanding even after switching the battery current direction.